Mutation in ADORA1 identified as likely cause of early‐onset parkinsonism and cognitive dysfunction. Issue 7 (2nd May 2016) - Jaberi, Elham; Rohani, Mohammad; Shahidi, Gholam Ali; Nafissi, Shahriar; Arefian, Ehsan; Soleimani, Masoud; Moghadam, Abolfazl; Arzenani, Mohsen Karimi; Keramatian, Farid; Klotzle, Brandy; Fan, Jian‐Bing; Turk, Casey; et al.
ABSTRACT: Background: We aimed to identify the genetic cause of neurological disease in an Iranian family whose manifestations include symptoms of parkinsonism and cognitive dysfunction. Methods: Clinical data on the patients were gathered by interviews with parents, neurological examinations, and laboratory tests. Genetic analysis was performed by genome‐wide single‐nucleotide polymorphism homozygosity mapping and exome sequencing. The effect of putative disease‐causing mutation was assessed by immunocytochemistry on HEK293 cells and Western blotting on proteins extracted from HEK293 cells transfected with wild‐type and mutated genes. Results: Homozygosity mapping and exome sequencing led to identification of a mutation in ADORA1 that causes p.Gly279Ser in the encoded protein, adenosine A1 receptor (A1 R), as the probable cause of disease. The mutation segregated with disease status in the family, affects a highly conserved amino acid, and was absent in 700 controls. Conclusions: The known biological activities of A1 R in brain functions including its physical interaction with and inhibitory effect on dopamine receptor D1 provide supportive evidence that disruptions of A1 R may result in neurological dysfunction. Also, recent evidence on the related adenosine A2B receptor marks the domain in which the mutation is positioned as important for function. Finally, ADORA1 is located within the Parkinson's disease locus PARK16, which has been identified in several populations. ADORA1 may be the PD susceptibility gene within this locus. The molecular mechanism by which p.Gly279Ser disrupts A1 R function remains unknown, but a quantitative effect on interaction with the dopamine receptor was not shown. © 2016 International Parkinson and Movement Disorder Society